2014
DOI: 10.1002/app.41363
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐tethered conjugated polymers created via the grafting‐from approach

Abstract: Polyacrylate brushes with pendent terthiophenes [poly(terthiophene methyl methacrylate) (PTTMM)] were successfully grown from indium tin oxide and gold with surface‐initiated atom transfer radical polymerization. The films formed on both substrates were characterized by ellipsometry and Fourier transform infrared spectroscopy. Using cyclic voltammetry, we electrochemically crosslinked the PTTMM brush to form a conjugated polymer network. The conjugation lengths in the film were increased as evidenced by ultrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…S7A †) was compared to the IR spectra of the thinner brushes obtained in nitromethane (140 nm) and dry chloroform (170 nm) ( Fig. 50 Unfortunately, pendant thiophene rings in the formed PMTM brushes could not be polymerized by the proposed electrochemical approach due to low reactivity as it was noticed by the authors. It was found that the average conjugation length was the largest for the 140 nm brush obtained using polymerization in nitromethane (see Fig.…”
Section: Influence Of Oxidative Polymerization Conditions On Brush Comentioning
confidence: 99%
“…S7A †) was compared to the IR spectra of the thinner brushes obtained in nitromethane (140 nm) and dry chloroform (170 nm) ( Fig. 50 Unfortunately, pendant thiophene rings in the formed PMTM brushes could not be polymerized by the proposed electrochemical approach due to low reactivity as it was noticed by the authors. It was found that the average conjugation length was the largest for the 140 nm brush obtained using polymerization in nitromethane (see Fig.…”
Section: Influence Of Oxidative Polymerization Conditions On Brush Comentioning
confidence: 99%
“…Most importantly, the delamination of the polymer layer from the surface can be eliminated. Very recently, Saha et al [43] reported the grafting of poly(terthiophene methyl methacrylate) (PTTMM) and poly(3-methylthienyl methacrylate) (PMTM) from gold and indium tin oxide (ITO) substrates via surface-initiated ATRP (Scheme 4). Moreover, the pendant terthiophene groups in PTTMM were electrochemically cross-linked to produce a conjugated polythiophene network.…”
Section: Atom Transfer Radical Polymerization (Atrp)mentioning
confidence: 98%
“…The hydroxyl function was also obtained by aldehyde reduction. In this way, methyl alcohol was obtained either in position 3′ [ 148 , 276 , 277 ], in position 3 [ 278 ], or in position 3 and 3″ [ 279 ], affording asymmetrical or symmetrical trimers with the alcohol group on the lateral units. An example of asymmetric trimer carrying alcohols on the lateral units is given by the works of the van Esch’s group, where the –OH terminated poly(ethylene glycol) chains are connected in position 3″ and 4 [ 280 , 281 ].…”
Section: Trimer Structuresmentioning
confidence: 99%
“…The alcohol [ 250 , 253 , 273 , 274 , 275 , 277 , 364 , 365 , 368 , 369 ] or the carboxylic acid [ 302 , 343 , 344 , 346 , 347 ] on the trimer is exploited for this purpose ( Scheme 19 , I and II). In this way, several molecules, nanoparticles and other functional materials were covalently linked to the trimers, including spyropyran [ 343 , 370 ], gold nanoparticles [ 371 ], poly(ethylene glycol) [ 302 , 372 ], cellulose [ 373 ], methaclyate [ 277 ], thiocarbonylthio derivate useful for RAFT (Reversible addition−fragmentation chain-transfer) polymerization [ 275 ] and olefin dendrons [ 374 ]. Numerous works report the preparation of the 3′,4′ trimer diester ( Scheme 19 , III) [ 242 , 361 , 362 , 366 , 375 , 376 ].…”
Section: Trimer Structuresmentioning
confidence: 99%